EFEKTIFITAS PEMASARAN MELALUI INSTAGRAM TERHADAP PENINGKATAN JUMLAH NASABAH PADA PT BANK SYARIAH INDONESIA KC JEMBER - Salsabilla, Zahratullidya Regita; Setianingsih, Wahyu Eko; Dewi, Ira Puspita (Relawan Jurnal Indonesia, 2023)
This research aims to test whether the promotions carried out by Bank Syariah Indonesia Jember through instagram are effective in increasing the number of customers. This study uses AIDA method as the variables namely Attention(X1), Interest(X2), Desire(X3), Action(X4). The problem raised in this study is that there are still many people with relatively low interest in saving in islamic banking because some people are not yet interested in choosing Islamic products over conventional products and because Islamic financial literacy in society is still low. Some of the deficiencies in the instagram account of Bank Syariah Indonesia Jember, such as the lack response from followers on each post, made reseacrchers interested in testing how effective the instagram acoount of Bank Syariah Indonesia Jember is in increasing the number of customers. The type of research used quantitative with descriptive research methods. The data collection method is through surveys and distributing questionnaires via Google Form and distributed to 80 respondents. The result of this study indicate that at the attention stage, the score is 77%, instrest is 77% desire 78%, action 77%. Based on the results of this study where all stages are in the good category, the results of this study are in accordance with the theory by Paulus (2012) that if the effectiveness valuereaches the 60%- 80% catgeory it is catgeorized good. This reflects that promotions through instagram carried out by Bank Syariah Indonesia Jember are well able to attract customers to use the products offered by Bank Syariah Indonesia Jember.